Analysis of global gravitational precursors before some Asian strong earthquakes - E. Khalilov; L. Wang; L. Khalilova (Геофизический журнал, 2019)
The authors consider the gravitational precursors of Mega Earthquakes in Asia and Southeast Asia: Sichuan earthquake, M7.9, May 12, 2008; Andaman Islands earthquake, M7.5, August 10, 2009; Samoa Islands earthquake, M8.1, September 29, 2009; Northern Sumatra earthquake, M7.8, April 06,2010; Tohoku earthquake, M9, March 11, 2011. All gravitational precursors were recorded using of ATROPATENA earthquake prediction stations. The creation of an international earthquake prediction system based on the results obtained is proposed. To monitor spatio-temporal variations of the gravitational field, special detectors named ATROPATENA stations have been developed and made. The detectors continuously measure the value of the gravitational constant G in mutually perpendicular directions and relative values of gravity Δg. Before and after the Mega Earthquakes in Asia and Southeast Asia, variations of the Earth’s gravitational field were registered at large distances from the epicenter (near 8000 km); they were measured with the ATROPATENA stations in the following location: Baku (Azerbaijan) and Yogyakarta (Indonesia). Indications of the Cavendish balance when measuring the gravitational constant G are influenced by spatio-temporal changes in external gravitational fields of geological origin, which alter over time indications of the true values of G. Measuring the true value of the gravitational constant G on the Earth’s surface with accuracy greater than the second digit after the decimal point is not possible due to the spatio-temporal variations of the gravitational field as a result of the impact of geodynamic processes.